The Library / Muhammad Fawwaz Muhammad Iqbal and Nur Balqis Muhammad Iqbal - Muhammad Iqbal, Muhammad Fawwaz; Muhammad Iqbal, Nur Balqis (Faculty of Computer and Mathematical Sciences, 2022)
Library is a place that always been a preferred choice for teachers and student as an alternative space for learning and discussion. While the interest of student using the library is growing, have you ever been in a situation where teachers need to compete with other class to book the space in the library, or students need to wait for a long queue to loan a book? Well, this is a common problem faced by teachers and student especially in boarding school as there is no effective digital management of library that can be viewed online. The library application is an initiative project which aims in developing a system to maintain all the daily work of library in digital online format. This application has many features which are generally not available in normal library management such as a function for teachers to reserve study spot for their students online. This will help teachers to manage and find the best timing via digital application without need to physically to go to library to book the space. It has also a facility where student can see list of books online and perform book loan swiftly, view list of books issued to them and its issue date and return date, also can view announcement or competition made by school management and submit their interest to join in effortlessly. Overall, this project application is being developed to help the teachers and students as well as the library staff to maintain the library in the best way possible and to reduce the human efforts.